Kajian Aplikasi Efek Dingin Udara Subuh untuk Pengkondisian Udara Ruangan; Studi Kasus di Kota Medan - Himsar Ambarita (Jurnal Dinamis, 2012)
AbstractIn recent years, residential and comercial buildings in typical city of Indonesia such as Medan consume a huge amount of high grade energy for ventilation and air conditioningsystems. Air conditioning system, renewable energy powered, is expected to play an importantrole in order to reduce high grade energy consumption. The present study promotes theposstibility of using the cooling effect resulting from ambient temperature in daybreak. Thewater is cooled by ambient as a thermal cold storage, the cool water is then transfer into theconditioned space. The measurements of the following parameters ambient temperature,relative humidity, solar radiation, wind speed have been performed using HOBO microstation inevery minute for 3 months. The results show that ambient in daybreak can provide coolingwater with temperature of lower than 23oC. Commercial CFD is used to simulate coolingprocess by using this cold water. The simulation results shows that maximum ambienttemperature of 30.39oC can be cooled up to 26.1oC. In other words, the maximum temperaturein the room can be decreased in order of 4.8oC. The main conclusion can be drawn here is thatcooling effect in the ambient temperature can be used to provide cooling air for conditionedroom.Keywords: Zero Energy Building, Natural Cooling, CFD